Pemikiran Pendidikan Abu Hamid Muhammad Bin Muhammad Al-Ghazali - Sherly Quraisy; Khoirul Holis; Mohammad Hasan (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2023)
In the Islamic worldview, learning holds significant meaning, as it is an integral part of human existence. Learning activities play a crucial role in education, as they involve the interaction between educators and students. Notably, Imam Al-Ghazali, a prominent Islamic scholar and educator, contributed significantly to the study of learning activities and the development of Islamic educational thought in his time. However, in contemporary times, many educators and students, particularly in Islamic Religious Education, tend to uncritically adopt the Western education concept and neglect the teachings of Islamic scholars like Imam Al-Ghazali. Imam Al-Ghazali, renowned as a Sufi scholar, provided monumental works in various areas of Islamic studies, including education. His thoughts and teachings were influenced by Sufi values, emphasizing the integration of Islamic teachings in learning and education. Al-Ghazali viewed learning as a means of worship and seeking the pleasure of Allah. He believed that the learning process was a spiritual journey to comprehend the essence of knowledge, shape behavior, and draw closer to Allah for worldly and ultimate salvation.